2013
DOI: 10.1002/lt.23619
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib delays recurrence and metastasis after liver transplantation in a rat model of hepatocellular carcinoma with high expression of phosphorylated extracellular signal-regulated kinase

Abstract: Liver transplantation (LT) is one of the curative treatments for hepatocellular carcinoma (HCC). However, cancer recurrence and metastasis after LT are common in some HCC patients with high-risk factors (even in those within the Milan criteria). It remains unclear whether adjuvant therapy with sorafenib inhibits HCC recurrence and metastasis after LT. Therefore, we performed orthotopic LT in an August Irish Copenhagen (ACI) rat model of HCC. Because LT involves immune rejection and tolerance and it is unknown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Sorafenib have shown to delay HCC recurrence and metastasis after LT in a rat model [137] . In a prospective not randomized pilot study, 7 patients with HCC above Milan criteria were treated with sorafenib after LT, and compared with 12 matched historical controls in whom sorafenib had not been used [138] .…”
Section: Strategies To Improve Outcome After Liver Transplantationmentioning
confidence: 99%
“…Sorafenib have shown to delay HCC recurrence and metastasis after LT in a rat model [137] . In a prospective not randomized pilot study, 7 patients with HCC above Milan criteria were treated with sorafenib after LT, and compared with 12 matched historical controls in whom sorafenib had not been used [138] .…”
Section: Strategies To Improve Outcome After Liver Transplantationmentioning
confidence: 99%
“…However, patients who undergo LT have a high risk of tumor recurrence due to long-term use of FK506; whereby subsequent administration of immunosuppressive drugs may accelerate the risk of mortality (13,25). Although current treatments for post-LT recurrence in patients with advanced HCC has limited efficacy (2,5,811), the recent ‘SiLIVER’ study demonstrated that SRL may act as an efficacious immunosuppressive drug and an antineoplastic agent for LT patients, with favorable clinical safety and efficacy comparable to that of FK506 (13).…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplantation (LT) is currently the most viable and effective treatment option for patients with hepatocellular carcinoma (HCC) except for surgical resection, thus it may be used for patients where resection is not an option (1). Although the implementation of the Milan and University of California at San Francisco (UCSF) criteria has improved post-LT survival rates, patients who do not fit the UCSF criteria currently undergo LT worldwide (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, tumor size, number, histological grade of differentiation, microvascular and macrovascular invasion, alpha-fetoprotein and ischemia time are well-known predictors of HCC recurrence after OLT. [5][6][7][8][9][10] Recently, adjuvant therapy with sorafenib 11 and obesity 12 was shown to be related to post-transplantation recurrence.…”
Section: Introductionmentioning
confidence: 99%